Market Development and Differential Product Analysis for Business Sustainability of an SME in Moslem Fashion Industry - Diena Yudiarti; Bijaksana Prabawa; Rizki Yantami Arumsari; Denta Aulia Farihah (Research Synergy Foundation, 2024)
The diversity of creative industries provides benefits to society in general and business to foster creativity and innovation, which is supported by various natural and human resources. Of the 17 creative economy sub-sectors, fashion is developing rapidly, occupying the second position in contributing 18.15% of the total 75% PDM of the creative economy. The fashion industry’s growth in Bandung is quite high; however, it creates high market competition. For this reason, each fashion industry is competing to create innovation and uniqueness to differentiate each product and considers market development strategy as a strategy for the sustainability and growth of its business. Background of the research is the need for Y-Fashion design strategy. Y-Fashion (alias) is a fashion SMEs established in 2019 that has succeeded in producing a variety of products, and the owner decided to create a differentiation strategy for market development and product innovation as the purpose of this study. This research focuses on the Y-Fashion needs to be carried out to the strategy needed to realize its needs and uses strategy design formulation as the method research. The research method used was the collection of primary and secondary data collected by the research team from various stakeholder sources from Y-Fashion itself. Data analysis used a SWOT analysis with a focus on client needs (Y-Fashion) to suggest the right design strategy for the realization of its differentiation strategy. Analysis of the design strategy serves as input for the design of several media that are expected to assist Y-Fashion in responding to market developments and business innovations as the outcome of this study.